Luke's Jewish eschatology the National Restoration of Israel in Luke-Acts - Oliver, Isaac W. 1980- (New York, NY Oxford University Press, 2021)
"The following book investigates Luke's perspective on the salvation of Israel in light of Jewish restoration eschatology. It situates Luke-Acts in the aftermath of the destruction of the Second Temple in 70 CE. The author of Luke-Acts did not write the Jews off but still awaited the restoration of Israel. Luke conceived of Israel's eschatological restoration in traditional Jewish terms. The nation of Israel would experience liberation in the fullest sense, including national and political restoration"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Kingdom of God -- Biblical teaching; Israel (Christian theology) -- Biblical teaching; Eschatology, Jewish